Preparasi dan Investigasi Komposit Poliakrilamid-Kiserit-Selulosa Sebagai Pupuk Urea Lepas Lambat - Maliya Syabriyana Maliya Syabriyana (Jurnal Serambi Engineering, 2016)
The spread of contamination to ground water and surface water from excessive fertilizer become major concern. Therefore, the aim of this study was to develop slow release fertilizer using urea fertilizer and kieserite in polyacrylamide-cellulose composite.Composite preparation was carried out by two variables that are kieserite mass variation and cellulose mass variation. The compositequality as slow release agent is measured by characterizationanalysisincluding porosity, swelling power, adsorption of urea, and urea released profile from composite compared to urea granules and tablets. Functional cluster and bond was investigated by FTIR (Fourier Transform Infra Red). Adsorption and desorptionpower of composite was determined by UV-Vis spectrophotometer with Nessler method. Result of variations in kieserite shows that the addition up to 3 grams kieserit mass causes an increasing in the swelling and porosity.Addition of cellulose increased the swelling power of composite but it lowers the porosity of the composite. Testing adsorption and desorption performed on the composite of the best(of 2 g kieserite, 0,15 g cellulose, and kieserite mesh -60 +80). The adsorption of urea by composite is 2.3115 g urea/g composite. Release profile of urea from composite is slower than the urea granules or tablets. As result, polyacrylamide-kieserit-cellulose can be developed as slow release fertilizer to increase fertilizer using efficiency and to avoid excessive water and ground contamination